MANAGEMENT OF ORBITAL TUMORS PRESENTING AS UNILATERAL EXOPHTHALMOS - Mihai Liviu Ciofu; Daniela Șulea; Andrei Nicolau; Constantin Grigoraș; Mihaela Dana Turliuc (Romanian Journal of Oral Rehabilitation, 2018)
Aim of the study. We aim to present our experience regarding the management of exophthalmos as the first clinical manifestation of a space-occupying orbital lesion. Material and methods. We performed a retrospective review, selecting 17 patients with orbital tumors that initially presented for proptosis. Results. Following multidisciplinary clinical and imaging evaluation, three primary orbital tumors were diagnosed, one mass pertaining to the lacrimal gland, and 13 secondary tumors. Surgical treatment was performed in 11 patients. Complete excision was performed in three benign tumors, complete removal and orbital content preservation was achieved in eight patients, orbital exenteration was necessary in two cases of orbital malignancies, and extended orbital exenteration was performed in one patient. Four cases did not have indication of surgery due to internal carotid artery invasion or extensive intracranial invasion. Two patients were diagnosed with lymphoma following biopsy and underwent oncologic treatment. Conclusion. An early diagnosis of an orbital mass presenting as proptosis involves multidisciplinary evaluation for the exclusion of other causes of exophthalmos. Orbital content and function preservation are the main goals of the surgical treatment.